DIGITAL TRANSFORMATION TO IMPROVE THE WELL-BEING OF JUNIOR HIGH SCHOOL STUDENTS IN THE TIME OF COVID 19 IN SMPN AND PRIVATE SMP IN YOGYAKARTA - Muhammad Zuhaery; Dian Hidayati; Badrul Tamam (Jurnal Administrasi Pendidikan, 2022)
This study aims to examine the preparation, implementation and evaluation of digital transformation to improve student welfare during the COVID-19 period at Public and Private Middle Schools in Yogyakarta. This research approach uses qualitative data analysis techniques using directed interview techniques, participant observation, data presentation and drawing conclusions. The results of the study show that the planning used by Public and Private Middle Schools in Yogyakarta in digital transformation improves student welfare, among others by adjusting the curriculum used and using a simple curriculum during the COVID-19 response. The implementation used by Public and Private Middle Schools in Yogyakarta in digital transformation improves student welfare, including by using various internal school LMS (Learning Management System) platforms, ensuring the smooth running of students and presenting student welfare. Evaluations used by Public and Private Middle Schools in Yogyakarta in digital transformation to improve student welfare include: (1) bridging parents regarding child development; (2) make an assessment that can be used as a basis for evaluating children's learning; and (3) provide many opportunities for input into schools so that evaluation makes learning fun.